Impact of Dental Neglect Scale on Oral Health Status Among Different Professionals in Indore City-A Cross- Sectional Study - Sarkar, Pubali (J Clin Diagn Res, 2015)
BACKGROUND: Young educated Indian generation are very much health conscious. They take adequate nutritious balanced diet and practice physical exercise regularly to keep themselves active and healthy. Oral health is a part of general health care system. If oral health is neglected it may affect our general health and as a result it affects our quality of life too. AIM: To assess dental negligence and oral health status by using Dental Neglect scale questionnaire among different professionals of Indore city. MATERIALS AND METHODS: The study consisted of a convenient sample of 400 students of aged 18-25 years from 4 different professional colleges of Sri Aurobindo Group of Institutes of the same campus. A pretested validated questionnaire was used for assessing dental neglect and home dental care practices. Oral health examination was conducted to assess dental caries and oral hygiene status by using DMFT and OHIS respectively. Data was analysed using SPSS Software (version 20). RESULTS: For OHI(S), majority of the respondents (57.7%) showed fair oral hygiene for DNS score <15, whereas majority of the professionals (63.7%), showed poor oral hygiene for DNS score >15. The Dental Neglect Scale (DNS) score was found statistically significant with OHIS and caries experience at 95% Confidence Interval. There was no statistically significant difference between DNS score and frequency of Decayed, Missing and Filled teeth DMFT. CONCLUSION: The Dental Neglect Scale appears to be a sound method for objectifying dental neglect. It has many of the features of a satisfying health index. However, further validation with other age groups, cultures, place and a larger population is required in order to justify the utility of Dental Neglect Scale in different situations.